Assessment of exposure to polycyclic aromatic hydrocarbons in engine rooms by measurement of urinary 1-hydroxypyrene. Issue 10 (October 1996) - Moen, B E; Nilsson, R; Nordlinder, R; Ovrebø, S; Bleie, K; Skorve, A H; Hollund, B E
Abstract : OBJECTIVE: Machinists have an increased risk of lung cancer and bladder cancer, and this may be caused by exposure to carcinogenic compounds such as asbestos and polycyclic aromatic hydrocarbons (PAHs) in the engine room. The aim of this study was to investigate the exposure of engine room personnel to PAHs, with 1-hydroxypyrene in urine as a biomarker. METHODS: Urine samples from engine room personnel (n = 51) on 10 ships arriving in different harbours were collected, as well as urine samples from a similar number of unexposed controls (n = 47) on the same ships. Urinary 1-hydroxypyrene was quantitatively measured by high performance liquid chromatography. The exposure to PAHs was estimated by a questionnaire answered by the engine room personnel. On two ships, air monitoring of PAHs in the engine room was performed at sea. Both personal monitoring and area monitoring were performed. The compounds were analysed by gas chromatography of two types (with a flame ionisation detector and with a mass spectrometer). RESULTS: Significantly more 1-hydroxypyrene was found in urine of personnel who had been working in the engine room for the past 24 hours, than in that of the unexposed seamen. The highest concentrations of 1-hydroxypyrene were found among engine room personnel who had experienced oil contamination of the skin during their work in the engine room. Stepwise logistic regression analysis showed a significant relation between the concentrations of 1-hydroxypyrene, smoking, and estimated exposure to PAHs. No PAHs were detected in the air samples. CONCLUSION: Engine room personnel who experience skin exposure to oil and oil products are exposed to PAHs during their work. This indicates that dermal uptake of PAHs is the major route of exposure.